To Be or Not To Be in Office Again, That is the Question Political Business Cycles with Local Governments - Baleiras, Rui (2019)
Most opportunistic-type models of political business cycles tend to posit a given objective for incumbents: maximisation of re-election chances. Though taking an opportunistic view too, we suggest a new explanation for a fiscal policy cycle: the incumbent’s concern with her own welfare in cases of victory and defeat. This rationale addresses local policy-making in particular. An equilibrium perfect foresight model is designed which totally dispenses with any form of irrationality (namely, on the part of voters) or the common objective functions (re-election chances). Being well grounded in basic microeconomic theory (welfare maximisation by the individual agent), our model provides another foundation for the emergence of political business cycles at the local level. The empirical plausibility of theoretical predictions is then tested on Portuguese municipal data ranging from 1977 to 1993. The estimation of an error-components econometric framework finds evidence in favour of the proposed explanation and enlightens the role played by several politicoeconomic determinants of local governments’ investment outlays, such as electoral calendar, re-candidacy decisions, political cohesion and intergovernmental capital transfers.